Theoretical Demonstration of Security Improvement of Optical Phased Array Based on Optically Injection-Locked Lasers - Anh-Hang Nguyen (MDPI AG, 2021)
The high security of optical phased array (OPA) signals is an important requirement for OPA-based optical wireless communication (OWC). We propose a method for improving the security of OPA-based OWC systems using optically injection-locked (OIL) semiconductor lasers. We theoretically demonstrate the amplitude and phase modulation of OIL-OPA elements by controlling the injection-locking parameters of the OIL lasers. When a Taylor window function is applied as the amplitude profile of the OPA transmitter, the sidelobe level decreases by 22 dB and the unsecured distance reduces 10 times compared to the case without the Taylor window function. In addition, the unsecured area factor becomes 0.8%.